The function of theory of constructional perceptions in Allamah Tabatabaii's socio-political thought - Abdul Rasoul Hassanifar (Pizhūhish/hā-yi Falsafī- Kalāmī, 2017)
Given its depth and width, Allamah Tabatabaii's socio-political thought can solve many current political problems in different societies. The theory of constructional perceptions is one of the most important foundations of his philosophical thought, which has exerted influence on his socio-political thought and somehow determines the orientation of his views. Considering the importance and necessity of discussing Allamah Tabatabaii's socio-political thought and its foundations, the present paper seeks to study the foundations and cognitive hypotheses of  his political thought, one of the most important of which is the theory of constructional perceptions on the one hand, and the function of such an approach in socio-political thought, that is, how Allamah Tabatabaii views different political problems in the society including the origin of socio-intellectual difficulties, man, society, government and its ideal form, rule, justice and economy, on the other hand. It concludes that Allamah Tabatabaii's socio-political thought influenced by the theory of constructional perceptions has some capabilities based on which it opens a new space in the world of politics while being distinctive from relativistic thoughts, and has some results and functions which provide solutions for many current problems based on accepting multiplicity and change while being committed to the essential principles of Islam.